Administrative Services for Making Marriage Certificates at the Office of Religious Affairs, Sirah Pulau Padang District, Oki Regency - Nopianto, Usman (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
This research was conducted with the aim of knowing the administrative service process for making marriage certificates at the KUA, Sirah District, Padang Island. The method used in this study is a qualitative descriptive method in which a method related to data collection, while the data used are: interviews and observations. From the results of interviews conducted with the Head of KUA, administration, and Administration, the results of the research conducted indicate that the administrative service process for making Marriage Certificates is still low, this is due to the fact that there is only one employee in charge of administration, and the lack of implementation of guidance services. and empowerment in planning activities in making Marriage Certificates.